EDUKASI DEMONSTRASI VIDEO ANIMASI TERHADAP KEMAMPUAN PSIKOMOTOR FIRST AID ANKLE SPRAIN PADA KOMUNITAS SEPAK BOLA DI DESA MEKIKIS - Didit Damayanti; Widyasih Sunaringtyas; Eka Septiani (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Sports activities have a risk of injury and are the most common cases. An ankle sprain is one of the acute injuries to the musculoskeletal system that is often experienced by teenagers when they play or during sports activities. Inappropriate early management of ankle sprain injuries disrupts ankle function and can delay recovery time. First aid for ankle sprains uses the Rest, Ice, Compression, and Elevation (RICE) method. The purpose of this study was to determine the effect of the video animation demonstration educational method on first-aid ankle sprains in the soccer community in Mekikis Village. This study used a pre-experimental design with a one-group pre-test-post-test design approach. The population of 70 respondents used purposive sampling with a sample size of 23 respondents. Performed for 30 minutes and two times the intervention. The results showed that the pre-test results of all respondents were in the less category. Most of the post-test results were in a good category. The results of data analysis used the Wilcoxon signed rank test P value 0.000 <0.05, which means that there is an influence of educational video animation demonstration on the ability of first aid ankle sprains in the soccer community in Mekiki Village. The researcher believes that giving material using the EDEVIA method is effective in improving the psychomotor abilities of first-aid ankle sprains in members of the soccer community because it uses animated video demonstration media that uses two senses at once, namely hearing and sight, so it is easy to understand and more interesting. Factors that affect the increase in ability scores are age, education, experience, and information. It is better if members of the soccer community can apply independently if they encounter a case of an ankle sprain.